A rapid method for quantifying small‐scale vegetation patch structure to complement conventional quadrat surveys. Issue 3 (22nd September 2021) - Butler, Liam; Sanderson, Roy A.
Abstract: Aims: Vegetation sampling typically involves the use of quadrats to estimate species cover abundance. Such surveys do not generally record small‐scale vegetation patch structure at sub‐quadrat scales. Here we test a simple method to quantify patch structure that complements conventional techniques. We compare the two methods, and analyse metrics derived from small‐scale patch surveys with environment/management data. Location: Northumberland, United Kingdom. Methods: We recorded cover abundance of all species in an upland moor with 1‐m 2 quadrats. These were divided into 100 'sub‐quadrats', 10 cm × 10 cm, and the dominant and subdominant species identified. Patch metrics (number, area and shape) for individual species recorded as dominant or subdominant in the subquadrat survey were analysed using multi‐variate generalised linear models with environmental and management data. Sub‐quadrat data were also aggregated for each quadrat, to create species composition data. The two sets of compositional data, from whole‐quadrat and sub‐quadrat aggregations, were compared via Procrustes rotation of ordination scores. Results: Patch number, area and shape for dominant and subdominant species were all significantly affected by soil pH, soil water content, slope and elevation. Effects of proximity to sheep tracks and drainage ditches were less consistent amongst species. Ordinations of vegetation data from conventional and sub‐quadrats were similar, with significant Procrustes R 2 of 67% and 70% for dominant and subdominant species respectively. Conclusions: Sub‐quadrat surveys can easily be used to complement existing whole‐quadrat surveys at little cost in time or resources. Their patch metrics can provide additional insights into the environmental and management drivers that may affect the growth of individual plants or clumps, potentially in relation to plant traits, and thus alter the overall community composition. The methods we describe can readily be adapted to other sizes of quadrats and sub‐quadrats in a wide range of vegetation communities. Abstract : We describe a simple method to survey the patch structure of vegetation at small spatial scales that can be used in combination with conventional quadrat survey methods. We test this 'sub‐quadrat' method on upland vegetation in NE England, and demonstrate that it can provide additional insights into vegetation patterns, in relation to environmental and management conditions. The method is cost‐effective in time and resources, and can be easily adapted to other habitats.